Abstract: Mental Safety at Work – New Research and What It Means for Your Organisation - Sutherland, Dougal (New Zealand Journal of Health and Safety Practice, 2024)
Mental safety is at the foundation of psychological health and safety, making it of utmost importance for health and safety practitioners, business leaders, and managers to prioritise. In this presentation, we share research from a study aiming to better understand mental safety in Aotearoa New Zealand workplaces.